Peace Sociodrama: A Strategy to Reduce Junior High School Aggression - Salsabila Zihan Nurisma; Budi Astuti (Ridwan Institute, 2023)
Aggression behavior is one of the negative behaviors caused by the absence of self-control and emotional control. Another cause of aggression is the existence of conflicts both between individuals and between groups. Conflict occurs because of a sense of unpeace in individuals, so in this study aims to instill a sense of peace through sociodrama combined with the component of peace which is then called peace sodiodrama. Peace sociodrama is developed through research and development methods. The procedure used in this study was the borg and gall development procedure. Before developing the product, researchers measured the level of aggression and the results of these measurements showed a variety of aggression at the level of aggression at the level of rerndah at 30.9%, at a level less than 29.1%, at a moderate level of 43.6%, at a high level of 5.5%. Although low, aggression still exists in students in Yogyakarta and researchers believe that aggression behavior must be reduced, therefore peace sociodrama is developed as a strategy in reducing aggression. Peace sociodrama is developed in the form of manuals and implementation procedures. The results after product validity tests by material experts, media experts and peace sociodrama service experts fall into the category worthy of being used as a counselor strategy in reducing student aggressiveness